The Role of Infrastructure Investment in Economic Growth and Balanced Regional Development - N. V. Kapustina; A. I. Sadykov; J. Podhorský (Финансы: теория и практика)
The authors of the paper estimated infrastructure’ impact to economic growth, which affects the regional balanced development. The relevance of the research is substantiated by the growing dynamics of investment of public funds in infrastructure development of regions. The purpose of the research is to determine the impact of infrastructure investments on economic growth and balanced regional development. The objectives of the research are: assessment of the impact of investment in infrastructure, assessment of GRP, price index in the regions, assessment of the ratio of population by regions of Russia with average per capita incomes, wages, investment in infrastructure, renewal of fixed assets and assessment of parameters for the balanced development of regions. The authors used statistical research methods (panel data, regression analysis) to identify cause-effect relationships in the process of growth and balance of the regional economy. The scientific novelty of this paper is the identification of disproportions in development of regions in comparison with the contribution of infrastructure to the regional economy. The results suggest that the volatility of infrastructure investment across regions remains high, with the contribution of infrastructure to economic growth and balanced development (p-values from 0.6363 to 0.9552). The authors concluded that the importance of infrastructure investments is one of the most important factors in achieving socio-economic development of the region. Infrastructure investment needs to be supported to reduce regional imbalances.